A new antitrypanosomal alkaloid from the Red Sea marine sponge Hyrtios sp. (November 2018) - Shady, Nourhan; Fouad, Mostafa; Ahmed, Safwat; Pimentel-Elardo, Sheila; Nodwell, Justin; Kamel, Mohamed; Abdelmohsen, Usama
Abstract The antitrypanosomally active crude extract of the spongeHyrtios sp. was subjected to metabolomic analysis using liquid chromatography coupled with high resolution electrospray ionization mass spectrometry (LC–HR-ESIMS) for dereplication purposes. As a result, a new alkaloid, hyrtiodoline A (1 ), along with other four known compounds (2 –5 ) were reported. The structures of compounds1 –5 were determined by spectroscopic analyses, including 1D and 2D nuclear magnetic resonance (NMR) and high-resolution electrospray ionization mass spectrometry (HRESI-MS) experiments, as well as comparison to the literature. We further investigated the antitrypanosomal activity of the five compounds, where compound1 exhibited the most potent antitrypanosomal activity, with a half-maximal inhibitory concentration (IC50 ) value of 7.48 µM after 72 h.